Metabolic characteristics related to potentially toxic elements in the blood of young adults in China: a cross-sectional study - Zhang, Lei; Xu, Wen; Feng, Mingyu; Zhang, Jia; Wang, Zhenzhong; Kang, Wenfeng; Liu, Yi; Yang, Beibei; Guo, Yuming; Lu, Peng (Frontiers in Nutrition, 2025)
Epidemiological evidence links essential and potentially toxic metals exposure to impaired lung function, but underlying biological mechanisms remain unclear. Building on previous findings demonstrating impaired lung function from copper (Cu), cerium (Ce), and iron (Fe) exposure, this study explored associated blood metabolomic signatures in young adults. 1,742 first-year university students enrolled in 2019 were included in this study in Shandong Province, China. Whole blood metal concentrations (ICP-MS) and metabolomic profiles (LC–MS) were assessed. Metals were classified into quartiles and analyzed using ANOVA analysis and multiple linear regression to assess their association with metabolites. Metabolomic analysis identified Cu exposure significantly associated with 45 metabolites across 14 pathways. Ce exposure linked to 25 metabolites enriched in seven pathways. Fe exposure associated with 26 metabolites in 13 pathways. All three metals both dysregulated nicotinate and nicotinamide metabolism and vitamin B6 metabolism. Additionally, Cu and Ce disrupted unsaturated fatty acid biosynthesis. These findings reveal that specific metabolic pathways—particularly those involving nicotinamide and vitamin B6—may serve as potential nutritional intervention targets for mitigating metal-induced lung function impairment in young adults.